The Effect of Science Learning to Improve Critical Thinking Skills of Middle School Students: Literature Study - Annam, Syarful (Balai Publikasi Indonesia, 2023)
This study is a Literature Review article which aims to identify the most effective learning model for improving students' critical thinking skills in science learning. A search of literature study articles resulted in twenty-five articles that met the inclusion criteria and were relevant for review. The research results show that there are many learning models that can be applied in science learning to improve students' critical thinking skills. Of the 25 articles reviewed, there were 2 articles with an average critical thinking ability score in the 50-60 range, 3 articles in the 60-70 range, 13 articles in the 70-80 range, 5 articles in the 80-90 range and 2 articles in the range of 90-100. The research results show that the discovery learning model through science practicum activities is the most effective for improving students' generic science skills, characterized by the achievement of an average student score of 92.56.